Cell-to-Cell Communication and Vascular Dementia - Dietrich, Hans H. (2012)
Vascular Dementia (VaD) is the second most common form of dementia second only to that caused by Alzheimer's Disease. As the name indicates, VaD is predominantly considered a disease caused by vascular phenomena. In this opinion, we introduce the reader to recent developments in defining VaD as a unique form of dementia. We discuss the clinical and experimental evidence which supports the notion that the microcirculation, specifically cell-to-cell communication, likely contributes to the development of VaD. Through exploration of the concept of the neurovascular unit, we will elucidate the extensive cerebro-vascular communication which exists and highlight models which may help test the contribution(s) of cell-to-cell communication at the microvascular level to the development and progression of VaD. Lastly we explore the possibility that some dementia, generally considered to be purely neurodegenerative, may actually have a vascular component at the neurovascular level. This recognition potentially broadens the critical involvement of microvascular events that contribute to the numerous dementias affecting an increasingly larger sector of the adult population.